Syphilis associated with paretic neurosyphilis mimicking Reiter's syndrome in HIV-infected patients - Thales Costa Bastos; Daniela Cristina Caetano Maia; Nathália Matos Gomes; Carla Kellen da Silva Menezes; Valeska Francesconi; Fabio Francesconi (Sociedade Brasileira de Dermatologia, 2015)
Abstract HIV/syphilis co-infection is common because both conditions affect similar risk groups. HIV interferes with the natural history of syphilis, which often has atypical clinical features and nervous system involvement in the early stage of disease. We report the case of an HIV-positive patient with secondary syphilis, scaling palmoplantar keratoderma, scrotal eczema, balanitis and urethritis mimicking Reiter's syndrome. Immunohistochemistry using polyclonal antibodies against Treponema pallidum revealed the presence of spirochetes, associated with the paretic form of parenchymal neurosyphilis. The patient was given crystalline penicillin, with complete resolution of dermatological and neurological symptoms, and no sequelae.